The cradle-to-cradle (C2C) paradigm in the context of innovation management and driving forces for implementation - Viktoria Geng; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2014)
In the light of depleting natural resources and growing awareness for responsible consumption, Cradle-to-Cradle (C2C) has emerged as one of the key concepts redefining product characteristics and assigning a new role to environmental responsibility of companies. It reframes the general goal of reducing negative externalities in a more positive way seeking the design of healthy products made out of benign materials that circulate in an endless flow of resources after the use phase. The importance of the relatively new paradigm, coined by the chemist Braungart and architect McDonough, opens up new opportunities for companies and is already well established in practice. Considering the limited coverage of the topic in academia, especially in the context of innovation management, we aim to investigate the potential intersections between C2C and the Fuzzy Front End theory. Based on a case study research and a descriptive analysis of a dataset containing C2C certified products, we apply FFE success factors to C2C and derive enablers for successful C2C implementation.
Keywords: 330; cradle-to-cradle; eco-effectiveness; fuzzy front end